Hubungan Pengetahuan dan Sikap Terhadap Perilaku Pemilihan Skincare Wajah melalui Media Sosial pada salah satu Universitas Di Karawang Jawa Barat - Indah Laily Hilmi; Nalisha Putri Rianoor; Vesara Ardhe Gatera (Universitas Muhammadiyah Surakarta, 2022)
Skincare is needed to maintain skin cleanliness. When choosing skincare, some people were bad attitude and behavior only armed with social media, advertisement, and information form friends, which in reality is not necessarily true, so choose the wrong skincare. Internet connections and social networks make it easy to find information about the bought skincare. So it is necessary to know the description of knowledge, attitude, behavior and to prove the correlation between knowledge and attitude toward the behavior of choosing facial skincare through social media in one of University in Karawang-Wesy Java’s students. This study used a descriptive analytic design with a cross sectional approach. The instrument used is a questionnarie. The sample consisted of 392 students which included the inclusion criteria. The sampling technique used is accidental sampling. The results of the bivariate analysis used the chi square test and there is a correlation between knowledge toward the behavior of choosing facial skincare through social media with a significance value of 0,000 (p 0,05) and there is correlation between attitude toward the behavior of choosing facial skincare through social media with a significance value of 0,000 (p 0,05). The conclusions of this study there is a correlation between knowledge and attitude toward the behavior of choosing facial skincare through social media.